Hydrogen production from phenol steam reforming using nickel-cobalt modified titania coupled magnesium aluminate nanocomposite catalyst - Abbas, Tariq (2019)
Utilization of renewable and sustainable sources of energy has gained attention to replace conventional and non-renewable fossil fuels. Production of hydrogen by catalytic steam reforming of phenol (SRP) is anticipated to play a vital role to overcome energy demand in future. The objective of this study is to develop nickel (Ni) and cobalt oxide (Co3O4) supported titanium dioxide (TiO2) and magnesium aluminate (MgAl2O4) nanocomposite for SRP towards selective hydrogen production. Hydrothermal method was used to synthesize TiO2 microparticles (TMP), TiO2 nanorods (TNR), spinel MgAl2O4 and Co3O4 nanocubes. However, wet impregnation method was used to synthesise MgAl2O4-TNR and Ni/Co3O4 promoted MgAl2O4-TNR nanocomposite catalysts. The fresh and used catalyst samples were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, high-resolution transmission electron microscopy, field emission scanning electron microscopy, Brunauer-Emmet-Teller with nitrogen, Fourier transform infrared spectroscopy and thermogravimetric analysis to understand the crystallinity, electronic state, surface morphology, pore structure, surface area and stability. Initially, a systematic thermodynamic analysis (TDA) was conducted to investigate the effect of various process parameters on output products composition. Optimal equilibrium reaction conditions according to TDA were found to be 550-750 oC reaction temperature, 1 atmospheric pressure and 5 wt.% phenol concentration. The catalytic activity test over Ni/TMP, Ni/TNR and Ni-Co3O4/TNR was performed to investigate the role of Ni and Co3O4 on the effectiveness of different structures of TiO2 support for SRP using a vertically aligned stainless steel tubular fixed bed reactor at 700 oC and steam to carbon ratio (S/C) of 15/1 at atmospheric pressure. After detailed screening, 10%Ni-5%Co3O4/TNR catalyst showed phenol conversion of 92% and H2 yield of 83.5%. However, addition of MgAl2O4 as co-support with TNR promoted by Ni/Co3O4 was found very effective in phenol conversion with enhanced H2 yield and prolonged stability. Using composite catalyst, 96.4% phenol conversion with ~70% H2 selectivity and 88.6% H2 yield were achieved. The operating parameters were investigated by statistical approach using response surface methodology (RSM) to obtain optimum responses in the form of phenol conversion and H2 yield. Optimization of SRP by RSM revealed 92.5 % H2 yield at optimal operating condition of 781.7 oC, 10.15 ml/h feed flow rate, 7.2 wt.% phenol concentration and 0.312 g of catalyst loading. The stability test showed composite catalyst continued its catalytic activity even after 400 h. Therefore, it can be concluded that MgAl2O4-TNR promoted by Ni–Co3O4 catalyst has high prospective for application in steam reforming of phenol for selective and sustainable route for the production of hydrogen.